RELASI MUSLIM-BUDDHIS DI PANGGANG, GUNUNG KIDUL, D.I. YOGYAKARTA - Akmal Salim Ruhana (Harmoni, 2016)
As a multireligious country, Indonesia is facing the dynamic relation between majority and minority: between tension and harmony too. The potrait of Muslim- Buddhist relation in Panggang,Gunung Kidul, as historically observed, has shown a harmonious and unique interaction. This research tries to elaborate this condition. Through literature study, interview and observation, this research found that Muslim-Buddhist have a common basic need to build harmony, and they also have theological fundamental reason and strongly hold “cultural bonds“ of the ancient Java between them. There are also associational bond among lay people in society such as social gathering “sepuluhan” and volley ball team; and practising quotidian bond such as eating gathering in “sedekah bumi” and working together in “sambatan”. Those social bonding in each group does not bring to exclusivism but sthrengten their existence to hold mutual goals.